Prediction and simulator verification of state–space rotor modelling of helicopter manoeuvring flight - Gori, R.; Gennaretti, M.; Pavel, M.D.; Stroosma, O.; Miletovic, I. (My University, 2015)
Among the many fundamental components of a flight simulator, the mathematical representation of the vehicle dynamics stands out for complexity and importance. This is especially true for helicopters, for which the complex dynamics involved prevents simple models to be sufficiently accurate without the need of a certain amount of artificial tuning. In this work, a methodology to obtain a computationally efficient, finite-state representation of the aeroelastic response of helicopter main rotors suitable for realtime flight simulation is proposed. It is capable of introducing rotor dynamics effects usually neglected in models commonly applied to flight simulations. This rotor model has been implemented in the SIMONA Research Simulator at the Delft University of Technology, and the results obtained from dedicated flight tests carried out by two experienced pilots are presented and discussed.
Keywords: Flight Mechanics